PENGARUH PENAMBAHAN TEPUNG DAUN KELOR [Moringa oleifera] TERHADAP KADAR PROTEIN, KALSIUM, DAN DAYA TERIMA NUGGET IKAN LEMURU [Sardinella lemuru] - Maghfira Adistiya Pramono; Farida Wahyu Ningtyias; Ninna Rohmawati; Karera Aryatika (Persagi, 2021)
ABSTRACT Pregnant women are a group who is at risk of undergoing malnutrition. One effort to meet the nutritional needs of pregnant women is to modify dietary menus such as fish nuggets made from lemuru and moringa leaf powder to meet protein and calcium needs. The purpose of this study was to analyze the effect of adding moringa leaf flour to protein content, calcium, and acceptance of lemuru fish nuggets with the addition of moringa leaf flour. This type of research is Quasi-Experimental using the Completely Randomized Design (CRD) method, with the 12 experimental units in 4 treatments, addition of moringa flour to lemuru fish nuggets by 0, 20, 30, and 40 percent. Protein levels were analyzed using the Kjeldahl Semi-Micro method, calcium using the Permanganometric method, and the acceptability test using the Scale Test. data from the test results of protein levels and calcium levels were analyzed using the Kruskal Wallis test and the Mann Whitney U test, while the results of the acceptance test were analyzed using the Friedman test and the Wilcoxon Sign Rank test with a significance level of 5% (α = 0.05). The results showed that the addition of moringa leaf flour increased the protein and calcium content of lemuru fish nuggets, and had an effect on the taste acceptability of the nuggets (p-value ≥ α). Lemuru fish nuggets recommended are lemuru fish nuggets with the addition of 20 percent (X1) Moringa leaf powder, which contains 21.18 percent protein content and 410 mg calcium level. Lemuru fish nuggets with the addition of 20 percent moringa leaf powder (X1) contain protein content by SNI 7758: 2013. One-piece or 15 grams of lemuru fish nugget with the addition of 20 percent of moringa leaf powder(X1) can fill 29.28-34.16 percent of Recommended Dietary Allowances(RDA) of calcium is recommended for pregnant women aged 16-49 years. Consumption recommendations for pregnant women aged 16-49 years are 3-5 pieces per day to fill protein needs and 3-4 pieces per day to fill calcium needs. ABSTRAK Ibu hamil merupakan kelompok yang berisiko mengalami gizi kurang. Salah satu upaya memenuhi kebutuhan gizi ibu hamil dengan modifikasi menu makanan seperti nugget ikan berbahan lemuru dan tepung daun kelor untuk memenuhi kebutuhan protein dan kalsium. Penelitian ini menganalisis pengaruh penambahan tepung daun kelor terhadap kadar protein, kalsium, dan daya terima nugget ikan lemuru. Penelitian Quasi Experimental dengan metode Rancangan Acak Lengkap (RAL), terdiri dari 12 unit percobaan dalam 4 perlakuan, yaitu penambahan tepung daun kelor pada nugget ikan lemuru sebesar 0, 20, 30, dan 40 persen. Kadar protein dianalisis dengan metode Semi Mikro Kjeldahl, kalsium dengan metode Permanganometri, dan uji daya terima menggunakan Scale Test. Data hasil uji kadar protein dan kadar kalsium dianalisis menggunakan uji Kruskal Wallis dan uji Mann Whitney U Test sedangkan hasil uji daya terima menggunakan uji Friedman dan uji Wilcoxon Sign Rank dengan tingkat signifikasi 5% (α=0,05). Hasil penelitian menunjukkan penambahan tepung daun kelor meningkatkan kadar protein dan kalsium nugget ikan lemuru, dan berpengaruh pada daya terima rasa nugget (p-value ≥ α). Nugget ikan lemuru yang direkomendasikan adalah nugget ikan lemuru dengan penambahan tepung daun kelor sebesar 20 persen (X1) yang mengandung kadar protein 21,18 persen dan kadar kalsium 410 mg, kandungan protein sesuai dengan SNI 7758:2013. Setiap potong atau 15 gram nugget ikan lemuru dengan penambahan tepung daun kelor 20 persen (X1) dapat memenuhi Angka Kecukupan Gizi (AKG) sebesar 32,09 - 34,72 persen protein dan 29,28 - 34,16 persen kalsium untuk ibu hamil usia 16-49 tahun. Konsumsi 3-5 potong per hari mencukupi kebutuhan protein harian dan 3-4 potong per hari mencukupi kebutuhan kalsium harian untuk ibu hamil usia 16-49 tahun. [Penel Gizi Makan 2021, 44(1):1-10]